THE USE OF PODCAST AND ITS EFFECTIVENESS IN ELT: A SYSTEMATICS REVIEW : English - Putri Datin Hulliyany; Sefti Alifhiani; Nazini; Fatmiati; Tarihoran, Naf'an (ADIBA : JOURNAL OF EDUCATION, 2024)
Technology has contributed greatly to the world of education in this information age. Podcasts are an alternative learning media to support students' listening skills. In the development of ICT, Podcasts are digital recordings that contain recordings of event programs from television, radio, and interviews using the internet. This research aims to explore the use of podcasts and their effectiveness in ELT. By evaluating multiple journal articles released between 2018 and 2024, eighteen (18) papers were identified that meet the eligibility criteria for the study following the PRISMA 2020. The aim of this systematic review was to investigate the effectiveness of podcasts in English Language Teaching (ELT). The results showed that podcasts are an effective learning tool in English Language Teaching (ELT).